Integrating perceptions of safety and bicycle theft risk in the analysis of cycling infrastructure preferences (2021)
Cycling infrastructure development is an effective but expensive urban policy to encourage people to use bicycles. Although people usually prefer infrastructure with high cycling priority, authorities in some cities have focused policies on adapting part of current motor vehicle infrastructure to increase the length and coverage of bicycle infrastructure at the road level, which can help to lower infrastructure investment costs. Perceptions are also important in developing programs to promote cycling and they may even be more important for cyclists than the reality itself. In this research, we integrated the perceptions of cycling safety and theft risk into a hybrid discrete choice model in order to better understand cycling infrastructure preferences, using Bogota, a bike-friendly city with security concerns, as a case study. We found that concerns about safety are a significant deterrent to using bike lanes at the road level in the city while perceptions of theft risk affect the value or importance that bicyclists place on travel time. Based on modeling findings we proposed hard and soft measures to encourage bicyclists to use bike lanes at the road level.